A cross-sectional survey of Aedes aegypti immature abundance in urban and rural household containers in central Colombia (2017)
Background Aedes aegypti, the major vector of dengue, breeds in domestic water containers. The development of immature mosquitoes in such containers is influenced by various environmental, ecological and socioeconomic factors. Urban and rural disparities in water storage practices and water source supply may affect mosquito immature abundance and, potentially, dengue risk. We evaluated the effect of water and container characteristics on A. aegypti immature abundance in urban and rural areas. Data were collected in the wet season of 2011 in central Colombia from 36 urban and 35 rural containers, which were either mosquito-positive or negative. Immature mosquitoes were identified to species. Data on water and container characteristics were collected from all containers. Results A total of 1452 Aedes pupae and larvae were collected of which 81% were A. aegypti and 19% A. fluviatilis. Aedes aegypti immatures were found in both urban and rural sites. However, the mean number of A. aegypti pupae was five times higher in containers in the urban sites compared to those in the rural sites. One of the important factors associated with A. aegypti infestation was frequency of container washing. Monthly-washed or never-washed containers were both about four times more likely to be infested than those washed every week. There were no significant differences between urban and rural sites in frequency of washing containers. Aedes aegypti immature infestation was positively associated with total dissolved solids, but negatively associated with dissolved oxygen. Water temperature, total dissolved solids, ammonia, nitrate, and organic matter were significantly higher in urban than in rural containers, which might explain urban-rural differences in breeding of A. aegypti. However, many of these factors vary substantially between studies and in their degree of association with vector breeding, therefore they may not be reliable indices for vector control interventions. Conclusions Although containers in urban areas were more likely to be infested with A. aegypti, rural containers still provide suitable habitats for A. aegypti. Containers that are washed more frequent are less likely to produce A. aegypti. These results highlight the importance of container washing as an effective vector control tool in both urban and rural areas. In addition, alternative designs of the highly productive washbasins should continue to be explored. To control diseases such as dengue, Zika and chikungunya, effective vector breeding site control must be implemented in addition to other interventions.